Beyond the Biosphere: Decoding Bacterial Strategies at the Edge of Space - Hanan I. Malkawi; Almuthana K. Alkaraki; Amneh Alrabee; Hamzeh J. Al-Ameer; Mohamed Kayyali; Alaa A. A. Aljabali; Mohammad R. Rayyan (Journal of Pure and Applied Microbiology)
Microorganisms exhibit remarkable phenotypic plasticity in extreme environments, including the stratosphere. This domain poses significant challenges such as almost zero gravity and a pronounced deviation from the typical physical forces experienced by living cells. Studies have highlighted the resilience of terrestrial microorganisms, particularly bacteria, in conditions resembling outer space, exploring how bacteria acclimate to the harsh environment of the Earth’s stratosphere, marked by dryness, cryogenic temperatures, intense UV radiation, low pressure, and microgravity. This study encompasses various aspects of bacterial biology, including growth, morphology, physiology, and genetic profiles, to uncover the mechanisms behind their adaptation to microgravity. This exploration provides insights into the physiological adaptation of humans to space. This study involved exposing bacterial cells to microgravity conditions at an altitude of 33 km above Earth, achieved through a sealed container space capsule launched from a space balloon. This study highlights the capacity of terrestrial bacterial strains to thrive and adapt to such extraordinary conditions.